Important of Azoles (American International Journal of Biology and Life Sciences, 2019)
Azoles are one of a cyclic derivatives  of chemical  heterocyclic chemical and organic compounds including g a five member di unsaturated ring structure composed of  bi  nitrogen atoms at position (3 and 4) and one sulfur atom at position (1).